2013
DOI: 10.1089/bsp.2012.0069
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of High-risk Animal and Zoonotic Pathogens

Abstract: Preparedness for the decontamination of affected environments, premises, facilities, and products is one prerequisite for an immediate response to an animal disease outbreak. Various information sources provide recommendations on how to proceed in an outbreak situation to eliminate biological contaminants and to stop the spread of the disease. In order to facilitate the identification of the right decontamination strategy, we present an overview of relevant references for a collection of pathogenic agents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This article assessed the effectiveness of peracetic acid against spores of B. anthracis and B. cereus and vegetative forms of Y. pestis , B. mallei , B. pseudomallei , F. tularensis , B. abortus, and B. melitensis , confirming peracetic acid as a biocide and sporicidal agent of election against the main bacteria agents with potential bioterrorism use. 1 However, it must be emphasized that the tests conducted in this work were carried out at temperatures between 23°C and 30°C and that the sterilizing activity of peracetic acid at low concentrations and at short incubation times is less effective at higher temperatures. 29 In this regard, Kunigk and colleagues showed that at 45°C the effectiveness of peracetic acid decreases by 50% in 72 hours, while at 25°C the effectiveness decreases by 33% after 10 days.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This article assessed the effectiveness of peracetic acid against spores of B. anthracis and B. cereus and vegetative forms of Y. pestis , B. mallei , B. pseudomallei , F. tularensis , B. abortus, and B. melitensis , confirming peracetic acid as a biocide and sporicidal agent of election against the main bacteria agents with potential bioterrorism use. 1 However, it must be emphasized that the tests conducted in this work were carried out at temperatures between 23°C and 30°C and that the sterilizing activity of peracetic acid at low concentrations and at short incubation times is less effective at higher temperatures. 29 In this regard, Kunigk and colleagues showed that at 45°C the effectiveness of peracetic acid decreases by 50% in 72 hours, while at 25°C the effectiveness decreases by 33% after 10 days.…”
Section: Discussionmentioning
confidence: 98%
“… 1 , 3 , 20 , 21 Unfortunately, aqueous solutions of peracetic acid have short-term efficacy, because degradation processes cause a strong reduction of their activity. 1 , 4 Such instability is detected in the majority of products based on peracetic acid currently on the market. The rapid loss of activity is a disadvantage because, in order to be assured of the effectiveness of the treatment, operators are forced to reconstitute the product weekly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early control systems are in religious texts, which gives rules for the edibility of meat (Eliasi & Dwyer, ; Farouk, ). In this century in Europe, the European Commission has implemented a regulatory program 178/2002 to establish the general principles and requirements of food laws (Frentzel, Menrath, Tomuzia, Braeunig, & Appel, ), and all of the EU member states have had their own meat inspection systems long before the European common system. For example, in Finland, trichinella inspection started in 1867, and in addition to imported meat, domestic animals are controlled currently for presence of trichinella infection (Sukura, Nareaho, Mikkonen, Niemi, & Oivanen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many zoonotic diseases are major public and animal health problem and can impair the efficient production of food originated from affected animals and also the international commerce of related products, causing a great impact in economy . They are also responsible for decreased consumption of animal products and losses in tourism , as they may be considered a biological threat .…”
mentioning
confidence: 99%